Lost in the North: The first record of Diretmichthys parini (Post and Quéro, 1981) in the northern North Sea. (15th February 2017) - Cresson, Pierre; Rouquette, Manuel; Mirallès, Francoise Marco; Dufour, Jean Louis; Causse, Romain; Bouchoucha, Marc; Mahé, Kélig
Abstract: In June 2015, an individual of Diretmichthys parini (Post and Quero, 1981) was trawled at 530 m depth, in the North Sea off Norway and donated to research. This capture, the first for this species in the North Sea was the northernmost recorded so far, and provided an opportunity to document some aspects of the biology and ecology of this data-poor species. This individual was a female, 331 mm total length of 33 years old, with low mercury content in muscle and liver (~ 0.2 μg g − 1 wet mass). Stable isotope ratios (C and N) in muscle and liver were consistent with the planktonic diet expected for this species. The capture of this fish at the northern latitude known so far would be consistent with the extension of the home range and the latitudinal shift hypothesized for this species in the 1990′s.